Microalgae as Contributors to Produce Biopolymers - Madadi, Rozita (2022)
Biopolymers are very favorable materials produced by living organisms, with interesting properties such as biodegradability, renewability, and biocompatibility. Biopolymers have been recently considered to compete with fossil-based polymeric materials, which rase several environmental concerns. Biobased plastics are receiving growing interest for many applications including electronics, medical devices, food packaging, and energy. Biopolymers can be produced from biological sources such as plants, animals, agricultural wastes, and microbes. Studies suggest that microalgae and cyanobacteria are two of the promising sources of polyhydroxyalkanoates (PHAs), cellulose, carbohydrates (particularly starch), and proteins, as the major components of microalgae (and of certain cyanobacteria) for producing bioplastics. This review aims to summarize the potential of microalgal PHAs, polysaccharides, and proteins for bioplastic production. The findings of this review give insight into current knowledge and future direction in microalgal-based bioplastic production considering a circular economy approach. The current review is divided into three main topics, namely (i) the analysis of the main types and properties of bioplastic monomers, blends, and composites; (ii) the cultivation process to optimize the microalgae growth and accumulation of important biobased compounds to produce bioplastics; and (iii) a critical analysis of the future perspectives on the field.